Eksistensi Asuransi Syariah PT. Prudential Life Assurance - Dr. Djaenab Djaenab; Yusti Sari; H. Bolu Hasan Basri (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
This study aims to analyze how: (1) The existence of PT. Prudential Life Assurance Sharia Insurance; (2) What are the opportunities and challenges of Islamic insurance PT. Prudential Life Assurance. This research uses qualitative methods with an empirical approach. Primary data sources consist of informants from Managers and employees of PT. Prudential Life Assurance. Secondary data sources are taken from various reference books, journals, other scientific works as a theoretical basis. Data was collected using observation techniques, interviews, and documentation. The results of this study indicate that the existence of Islamic insurance PT. Prudential life assurance basically has been running for a long time which is marked by the development of Islamic financial institutions followed by the development of regulations regarding Islamic insurance. Opportunities and challenges for sharia insurance PT. Prudential Life Assurance to further develop, in addition to the large Muslim population of Indonesia, sharia insurance, especially PT. Prudential life assurance, is a choice in guaranteeing risks in life. While the challenges faced include a lack of human resources, the public does not fully understand the importance of insurance. The implication of this research is that it is hoped that managers, employees or agents will take the initiative again both in participating in training activities and outreach to the community, especially agencies. To minimize obstacles or challenges such as lack of public awareness and understanding of the importance of insurance.